Effect age of Ephestia kuehniella (Lepidoptera: Pyralidae) egg on biological and life table parameters of Trichogramma evanecens (Hymenoptera: Trichogrammatidae) - fatemeh Tabebordbar; parviz shishehbor; Ebrahim Ebrahimi (نامه انجمن حشره‌شناسی ایران, 2019)
Trichogramma evanescens Westwood is one of the most important biological control agents of lepidopteran pests. This parasitoid is widely distributed throughout Iran. Present study was conducted to assay influence of the age of Ephestia kuehniella Zeller egg on the number of parasitized eggs, developmental time, sex ratio, progeny longevity and fecundity of T. evanescens. Individual mated female parasitoids (E. kuehniella in no-choice experiments. Mean number of parasitized eggs were 32.40 ± 0.04, 29.80 ± 0.05, 26.93 ± 0.16, 23.83 ± 0.06 and 18.91 ± 0.04, respectively. The obtained results showed that different egg ages had a significant effect on the developmental time, sex ratio, progeny longevity and fecundity of the parasitoid wasp. Data analysis demonstrated significant decreasing of net reproductive rate (R0), intrinsic rate of increase (r) and finite rate of increase (λ) with increasing the age of eggs. The highest values for r and λ were 0.390 ± 0.006 day-1 and 1.47 ± 0.008 days, respectively in the eggs with 12h egg. The results of the current study indicated that the egg age is one of the most important factors on life table parameters of T. evanescens and the eggs of E. kuehniella with 12h age are the most suitable eggs for development, reproduction and mass rearing of T. evanescens.